Scaling climate-smart agriculture for accelerated agri-food systems transformation in Africa - Trautman, Sabrina; Chevallier, Romy; Cramer, Laura K.; Mutamba, Manyewu (African Union Development Agency, 2023)
This publication was prepared by the staff of the African Union Development Agency - NEPAD in partnership with experts from the Accelerating Impacts of CGIAR Research for Africa (AICCRA) Project, The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of AUDA-NEPAD. The designations employed and the presentation of material in this information product do not imply the expression of any opinion whatsoever on the part of AUDA-NEPAD concerning the legal or development status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The authors would like to thank wider AICCRA expertise that contributed towards this briefing paper, amongst others, Caroline Mwongera, Osana Bonilla-Findji, Sophia Huyer, Alison Rose, Desire Kagabo and Ivy Kinyua. The third Biennial Review (BR) of the Comprehensive Africa Agriculture Development Programme (CAADP), undertaken in 2022, revealed that countries are still falling short on meeting their national commitments towards agricultural transformation and climate resilience. In particular, the BR highlighted poor results in the commitment areas dedicated to reducing hunger, halving poverty, and enhancing the resilience of livelihoods and production systems in the face of climate variability and other related risks. In addition, the overall results of the BR illustrate that the pace at which implementation of CAADP is taking place on the ground is not good enough to lead to the intended food and climate goals of the continent. Emphasis therefore needs to be placed on tangible actions and intervention areas that can lead to accelerating CAADP implementation and directly support Africa in building its resilient food system. There is a large evidence base, and many country case examples, that highlight the key benefits that climate-smart agricultural (CSA) approaches and innovations can bring to the continent. Through enhanced planning, integration, ownership, implementation and scaling, CSA offers African countries practical solutions to realise the multiple goals set out in countries national agricultural and development plans, the CAADP Agenda, and more broadly within the continent’s Agenda 2063. This briefing paper provides practical guidance and key recommendations to member countries, and Africa at large, on implementing a comprehensive CSA approach. It discusses successful country cases and highlights the necessary enabling conditions for effective CSA scaling. It also suggests key areas of focus for countries hoping to adopt, scale and finance these innovative practices. These include activities to strengthen policy coherence, build capacity development and inclusion, enhance partnerships and dialogue, support research and development and market access, and increase financial provisioning.